Unusual “Knob-Like Chimney” Growth Forms on Acropora Species in the Caribbean - Rivera-Sosa, Andrea; Muñiz-Castillo, Aarón Israel; McField, Melanie; Arias-González, Jesús Ernesto (Frontiers in Marine Science, 2018)
This manuscript provides new insights on an unusual morphological plasticity growth form on Acropora spp. in the Caribbean. This abnormal knob-shaped growth is thought to be a progression from the damselfish “chimneys” that are commonly seen in coral-algal farms. However, the diameters of the observed knobs tend to be much larger on Acropora palmata, where they range from 1.37 to 5.44 cm in diameter, and they tend to be slightly smaller on A. prolifera, where they range from 1.1 to 2.72 cm in diameter. These knob-like chimney growths can affect entire colonies. The knobs are mostly covered with live tissue, while some knobs compete with turf algae. We hypothesize that these growths may be linked to stress from multiple predation and environmental conditions. Local stressors could synergistically influence the regeneration of scarred tissue and skeleton that result from predatory lesions, possibly leading to the formation of the knobs. Therefore, we provide preliminary data from a shallow reef site in coastal Honduras located within the Mesoamerican region where we found the knobs. To the best of our knowledge, the conditions that drive the occurrence of these unusual “knob-like chimneys” on Acropora spp. have not been previously assessed. Thus, we propose a series of guidelines to research the coral morphological plasticity that may be linked to this knob-like chimney phenomenon.